The Influence of PSB Application on the Growth of Aloe vera in a Verticulture Cultivation System - Handayani, Tri Suci; Rahmadina, Rahmadina; Selvia, Irda Nila (Jurnal Biologi Tropis, 2025)
Aloe vera is a tropical plant with significant potential to develop into a promising agricultural sector in Indonesia. To achieve high-quality Aloe vera harvests, it is important to pay attention to several growth conditions, especially plant care such as fertilization. This study aims to determine the effect of Photosynthetic Bacteria (PSB) fertilizer application and the effective dosage of PSB fertilizer for the growth of Aloe vera using vertical farming techniques. This research used a Non-Factorial Randomized Block Design (RBD), with treatment factors including: no application of PSB fertilizer (P0), PSB 5 ml/l (P1), PSB 15 ml/l (P2), and PSB 30 ml/l (P3). The research involved several stages of observation, including plant height, number of leaves, leaf width, leaf thickness, and root volume. The observed data were analyzed using ANOVA with the help of SPSS 26. If the ANOVA test showed a significant effect, further analysis was carried out using Duncan's Multiple Range Test (DMRT). The results showed that the application of PSB fertilizer had an effect on plant height (22.8 cm), leaf width (2.76 cm), number of leaves (7 leaves), leaf thickness (8.91 cm), and root volume (4 cm³). The best average treatment result for Aloe vera growth was obtained at a dosage of 15 ml/l (P2), indicating that Photosynthetic Bacteria (PSB) fertilizer at a dosage of 15 ml/l (P2) was sufficient to supply the necessary nutrients for the growth of Aloe vera.